Answers

  • Brainly User
2016-07-12T22:21:15+08:00
 \frac{1}{2}x  \frac{2}{3}  \frac{1}{3} (x+4)

LCD (Least common denominator) : (2)(3) ⇒ 6

Multiply each term by 6, then simplify:

(6) [ \frac{1}{2}x  \frac{2}{3}  \ \frac{1}{3} } (x+4)] (6)

3x + 4 = 2(x + 4)

3x + 4 = 2x + 8

3x - 2x = 8 - 4

x = 4     ⇒  Answer

Check, x = 4:

1/2 (4) + 2/3 = 1/3 (4 + 4)

2 + 2/3 = 1/3 (8)

6/3 + 2/3 = 8/3

8/3 = 8/3  (True)
0
Thank you again. thanks for always helping me with my assignments☺
This might be the last :-(
Why? help please? theres another one last help please? i already posted it
Please? I'm begging you Momgie